Entomological Risk Assessment for Dengue Virus Transmission during 20162020 in Kamphaeng Phet, Thailand - Thanyalak Fansiri; Darunee Buddhari; Nattaphol Pathawong; Arissara Pongsiri; Chonticha Klungthong; Sopon Iamsirithaworn; Anthony R. Jones; Stefan Fernandez; Anon Srikiatkhachorn; Alan L. Rothman; Kathryn B. Anderson; Stephen J. Thomas; et al. (My University, 2021)
Individual houses with high risks of dengue virus (DENV) transmission might be a source of virus transmission within the neighborhood. We conducted an entomological risk assessment for DENV transmission at the household level, comprising family cohort members residing in the same location, to assess the risk for dengue virus transmitted by mosquito vectors. The studies were conducted in Kamphaeng Phet Province, Thailand, during 2016-2020. Entomological investigations were performed in 35 cohort families on day 1 and day 14 after receiving dengue case reports. DENV was found in 22 Aedes samples (4.9%) out of 451 tested samples. A significantly higher DENV infection rate was detected in vectors collected on day 1 (6.64%) compared to those collected on day 14 (1.82%). Annual vector surveillance was carried out in 732 houses, with 1002 traps catching 3653 Aedes females. The majority of the 13,228 water containers examined were made from plastic and clay, with used tires serving as a primary container, with 59.55% larval abundance. Larval indices, as indicators of dengue epidemics and to evaluate disease and vector control approaches, were calculated. As a result, high values of larval indices indicated the considerably high risk of dengue transmission in these communities.
Keywords: Mosquito-borne diseases and control